Perception of body translation amplitude in altered gravity during parabolic flight - Clément, Gilles; Kuldavletova, Olga; Quarck, Gaëlle; Macaulay, Timothy R.; Wood, Scott J.; Denise, Pierre (Frontiers in Physiology, 2025)
IntroductionThis study aimed to assess how individuals perceive the amplitude of passive body translation in microgravity and hypergravity.MethodsSix subjects participated in parabolic flights aboard the Novespace A-310 Zero-G aircraft, performing tasks that involved linear translation ranging from 25 to 250 cm across different axes, all while blindfolded. After each motion stimulus, subjects reported their perceived displacement, while trial duration and movement amplitude and dynamics were recorded.ResultsResults showed that the perceived amplitudes of translations were accurate in 1 g. However, subjects significantly underestimated distances in 0 g and overestimated them in 1.8 g.DiscussionThese findings suggest that, in microgravity, the lack of gravitational cues disrupts the vestibular system’s ability to provide accurate information on body movement, leading to altered motion perception. The role of temporal cues in estimating movement, particularly when gravitational input is altered, is inferred since the reports were made following each trial. Countermeasures such as visual aids and proprioceptive devices could help astronauts improve distance and time estimates during long-duration missions, especially in vehicles with restricted visibility or when operating rovers on Lunar or Martian terrains.